Status of professional learning communities in developing countries: Case of Vietnam and Uganda - Doan Nguyet Linh; George Wilson Kasule (Institute of Advanced Engineering and Science, 2022)
What is the status of professional learning communities in Vietnam and Uganda? Is there a significant difference between the teaching experience of secondary teachers and how they see the relevance of professional learning communities on professional development in Vietnam and Uganda? The forementioned questions were explored by collecting data from secondary school teachers (n=345) in Vietnam and Uganda through a questionnaire. Descriptive statistics, analysis of variance (ANOVA) and Tukey honestly significant difference (HSD) were used to analyze the data. The findings depict that involvement of secondary school teachers in professional learning communities and the associated contribution on professional development is ‘moderate’ in Vietnam whilst, it is ‘minimal’ in Uganda. It was also established that significant difference exists between the teaching experience of secondary teachers and how they recognize the relevance of professional learning communities on professional development. The findings suggest that relevant educational policies and adequate funding ought to be considered in order to make professional learning communities vibrant in both Vietnam and Uganda. This is deemed key to enhance secondary school teacher competence which in turn could lead to higher students’ learning outcome in Vietnam and Uganda respectively.